Development of a Panel of Biomarkers for Differential Diagnosis of Multiple Sclerosis - Ovchinnikova, L. A.; Dzhelad, S. S.; Simaniv, T. O.; Zakharova, M. N.; Lomakin, Y. A.; Gabibov, A. G.; Illarioshkin, S. N. (Doklady. Biochemistry and biophysics, 2024)
Demyelinating diseases are a group of heterogeneous pathologies that affect the nervous system and reduce the quality of life. One of such diseases is multiple sclerosis (MS), an inflammatory autoimmune neurodegenerative disease of the central nervous system (CNS). At the initial stages, MS can mimic some infectious, neoplastic, genetic, metabolic, vascular, and other pathologies. Accurate differential diagnosis of this disease is important to improve the quality of life of patients and reduce possible irreversible damage to the central nervous system. In this work, we confirmed the possibility of using our previously proposed candidate panel of MS biomarkers to distinguish MS from neuromyelitis optica spectrum disorder (NMOSD) and amyotrophic lateral sclerosis (ALS). We have shown that our proposed panel (SPTAN1 601-644 + PRX 451-494 + PTK6 301-344 + LMP1 285-330 ) allows us to distinguish MS from ALS (AUC = 0.796) and NMOSD (AUC = 0.779).